BUILDING RESERVE COMPONENTS BASED ON STATE DEFENSE CAPABILITY AS INDONESIA’S DEFENSE POWER FACING NON-MILITARY THREATS - Indrawan, Raden Mas Jerry; Efriza, Efriza (Jurnal Pertahanan dan Bela Negara, 2018)
Indonesia’s Threats, Disturbances, Obstacles and Challenges (TDOC) in the future are considered non-military (non-conventional). Indonesia’s defense paradigm that is only relying TNI as a major force, should be changed. The drastic reduction of the military threats (conventional) from other countries to Indonesia, as well as similar threats around the world, make us have to rethink what is the appropriate formulation of Indonesia’s defense strategy in this era of nonmilitary threats. Therefore, the formation of reserve components, as previously has been equipped with competence and knowledge of state defense, needs to be considered more. The consideration is that the formation of this reserve components can be useful as a major defense element that support the main component, primarily to deal with non-military threats. The use of reserve components is not only prepared for war, but has a primary function for helping TNI deal with TDOC that is non-physical (intangible). This paper will discuss how the reserve components, as part of the nation’s defense force, faces future non-military threats. In addition, this paper also sees that state defense can be an integral part of the effort of the reserve components to make this happen. Keywords: state defense, reserve components, non-military threats